Role of insulin resistance and insulin action in polycystic ovary syndrome: a concept review - Kumari, Kirti; Babbar, Assem; Joshi, Yogesh (International Journal of Research in Medical Sciences, 2022)
Polycystic ovary syndrome (PCOS) is a highly prevalent endocrine-metabolic illness that has alarmingly high rates of infertility and other significant effects on the health of women. This review study highlighted that Insulin appears to damage every part of the hypothalamus-hypophysis-ovary axis, and insulin resistance in ovarian tissue leads to impaired metabolic signalling but intact mitogenic and steroidogenic activity, favouring hyperandrogenemia, which is thought to be the primary cause of the clinical symptoms of PCOS. This review also enumerates and briefly summarize the research methods related to effects of insulin resistance in PCOS, including molecular mechanism of action of insulin and anabolic processes that stimulate cell growth and differentiation; increase protein and fat storage; and the binding between α, β dimers and receptors on cell surface that results in alteration in gene expression, metabolism and growth.